PENGARUH NET PROFIT MARGIN DAN DEBT TO ASSET RATIO TERHADAP HARGA SAHAM PADA PT. INTILAND DEVELOPMENT, TBK. PERIODE 2011-2023 - Septy, Muhamad; Karolina (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to examine the influence of Net Profit Margin and Debt to Asset Ratio on the Stock Price of PT. Intiland Development, TBK during the period 2011 – 2023. A quantitative method was used to analyze and understand the partial or simultaneous effects of Net Profit Margin and Debt to Asset Ratio on Stock Price, and to determine which variable has the most dominant influence on the Stock Price of PT. Intiland Development, TBK. Data analysis utilized classical assumption tests, regression analysis, determination coefficient analysis, and hypothesis testing. From the data analysis results, it can be concluded that Net Profit Margin partially affects Stock Price, with a calculated t-value of 14.20349 > 2.228 t-table and a significance of 0.0337 < 0.05. Debt to Asset Ratio does not partially affect Stock Price, with a calculated t-value of 3.775690 > 2.228 t-table and a significance of 0.4378 > 0.05. Simultaneously, there is no influence between Net Profit Margin and Debt to Asset Ratio on Stock Price at PT. Intiland Development, TBK. This is evidenced by an F-value of 3.299264 < 3.71 with a significance value of 0.079369 > 0.05. This can also be seen from the R Square of 0.277, meaning that the variables Net Profit Margin and Debt to Asset Ratio contribute 27.7%, while 77.3% is influenced by other variables not explained in this study.